Poly(sulfobetaine methacrylate)-Modified Dimethylpolysiloxane with Improved Antibiofouling Property - Xu, Fengling; Lin, Cunguo; Zhang, Jinwei; Zheng, Jiyong; Wang, Li; Sun, Zhiyong (Asian Journal of Chemistry, 2013)
This paper describes a facile and novel approach for the surface modification of dimethylpolysiloxane membranes by introducing poly(sulfobetaine methacrylate) groups grafted via atom transfer radical polymerization (ATRP) for their resistance to protein-adsorption and diatom-adsorption. Chemical changes of the membrane surface were characterized by attenuated total reflectance Fourier transform infrared spectroscopy (ATR/FT-IR). Results revealed that poly(sulfobetaine methacrylate) groups have been successfully introduced to the dimethylpolysiloxane membrane surface. The surface properties of membranes were characterized by water-contact angle and protein adsorption measurements. It was found that the hydrophilicity was effectively improved and the bovine serum albumin adsorption was significantly suppressed by introducing poly(sulfobetaine methacrylate) groups. Finally, the diatom bioassays were measured further to evaluate the antifouling property for the studied membranes. Results showed that poly(sulfobetaine methacrylate)-modified dimethylpolysiloxane membranes had higher diatom-adsoption-resistance property. So the poly(sulfobetaine methacrylate)-modified dimethylpolysiloxane membranes have improved protein-adsorption-resistance and diatom-adsorption-resistance properties and should be potential marine antibiofouling materials.